Legal Implications Of Divorce Without A Trial On The Rights Of Divorced Couples - Tutu, Ratu Salsabila; Prahasti Suyaman (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to examine the legal implications of the practice of divorce carried out without going through a formal hearing in a religious court, especially on the protection of the rights of divorced couples. A valid divorce according to Indonesia's positive law can only be carried out before a panel of judges through a judicial process, but in practice, there are still many people who impose talaq orally or through communication without submitting an official application to the court. This study uses normative juridical methods with a qualitative approach, as well as interviews in Cibitung District to understand the factors that cause this phenomenon. The results of the study show that divorce without a trial has an impact on the loss of legal protection for the rights of couples. In addition, legally invalid divorces hinder the registration of new marriages due to the absence of divorce certificates. The main factors that affect this phenomenon include low legal understanding. Therefore, systematic efforts are needed to increase public legal awareness and expand access to justice, so that the divorce process can be carried out in accordance with positive law and provide fair protection for all parties.